PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN - Hidayat, Aris; Suwarsito, Suwarsito; Herawati, Niken (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research aims to identify and analyze the effect of the product quality and price variables toward customer’s satisfaction. Method of data collection in this research is using the survey method with questionnaires. Population in this research is student of Ganesa Vocational School. Based on the results of the analysis, it indicates that product quality has a significant effect on the customer’s satisfaction indicated by the t significant value 0.000 less than α =0.05. product quality and price significantly influence the customer’s satisfaction shown by F significant value of 0.000 smaller than α=0.05 and are able contribute to the customer’s satisfaction variables of 0.515 or 51.5 % the remaining 40.6% is influenced by other variables that are not examined in this research.